The [PSI+] prion exists as a dynamic cloud of variants. - David A Bateman; Reed B Wickner (PLoS Genetics, 2013)
[PSI(+)] is an amyloid-based prion of Sup35p, a subunit of the translation termination factor. Prion "strains" or "variants" are amyloids with different conformations of a single protein sequence, conferring different phenotypes, but each relatively faithfully propagated. Wild Saccharomyces cerevisiae isolates have SUP35 alleles that fall into three groups, called reference, Δ19, and E9, with limited transmissibility of [PSI(+)] between cells expressing these different polymorphs. Here we show that prion transmission pattern between different Sup35 polymorphs is prion variant-dependent. Passage of one prion variant from one Sup35 polymorph to another need not change the prion variant. Surprisingly, simple mitotic growth of a [PSI(+)] strain results in a spectrum of variant transmission properties among the progeny clones. Even cells that have grown for >150 generations continue to vary in transmission properties, suggesting that simple variant segregation is insufficient to explain the results. Rather, there appears to be continuous generation of a cloud of prion variants, with one or another becoming stochastically dominant, only to be succeeded by a different mixture. We find that among the rare wild isolates containing [PSI(+)], all indistinguishably "weak" [PSI(+)], are several different variants based on their transmission efficiencies to other Sup35 alleles. Most show some limitation of transmission, indicating that the evolved wild Sup35 alleles are effective in limiting the spread of [PSI(+)]. Notably, a "strong [PSI(+)]" can have any of several different transmission efficiency patterns, showing that "strong" versus "weak" is insufficient to indicate prion variant uniformity.